PERAN MAHASISWA DAN BANTUAN HUKUM BAGI MASYARAKAT - Alifah Herawati; Hartanto (JURNAL PANAH KEADILAN, 2025)
Students (undergraduate programs) have various titles, including agents of change and critical intellectual groups, in various histories of national struggles, as well as today, students are always at the forefront of change and struggle for society; In the context of legal aid, students are also expected to play an active role in realizing justice. The history of legal aid has existed since before independence, but its development can be said to be slow, while poor people often ignore their right to seek legal aid as seekers of justice. The right to obtain legal aid is the state's obligation to provide services to the community through various programs, as an embodiment of a legal state that respects human rights. In this post-reform era, it is worth discussing again what is the role of law faculty students in legal aid? This research uses normative research methods, namely Law no. 16 of 2016 concerning Legal Aid with the role of students in particular and the role of community organizations/advocates in general. On the other hand, legal assistance must also be provided by advocates and community organizations, with various requirements that must be met first.